An eco-friendly tanning process to wet-white leather based on amino acids. (10th October 2020) - Wu, Xiaohui; Qiang, Xihuai; Liu, Dou; Yu, Lidong; Wang, Xinke
Abstract: Chrome tanning has dominated in leather production up to now, while facing a significant challenge in terms of chromium and neutral salts. Therefore, greener and eco-friendly chemical material was explored and applied to tanning process in this research, in order to solve the problem of chromium and neutral salt pollution. The tanning process was optimized about tanning agent dosage, tanning temperature and time. The hydrothermal stability, physico-chemical and morphological characteristics, yellowing resistance were investigated in novel no-pickling tanning process for crust. And the eco-friendly impact of prepared materials and novel tanning process were also evaluated by biodegradation and environmental impact assessment (EIA). The results indicated that the hydrothermal stability of tanned leather for N, N′-di-(4, 6-dichloro-[1, 3, 5]-triazinyl)-2, 6-diaminohexanoic acid (L-Lys TCT)/2-(4, 6-dichloro-[1, 3, 5]-triazinyl-2-amino)-3-[4-(4, 6-dichloro-[1, 3, 5]-triazinyl-2-oxy)-phenyl]-propionic acid (L-Tyr TCT)/N, N′-di-(4, 6-dichloro-[1, 3, 5]-triazinyl)-2-amino-5-guanidyl pentanoic acid (L-Arg TCT) satisfied the basic demand of leather, and mechanical properties met the standard requirements for shoe upper. The scanning electron microscopy analysis further confirmed this point, which showed the regularity of grain and the evenly distributed fiber bundles. Meanwhile, the wet-white leather for L-Lys TCT has good yellowing resistance. Due to environmentally friendly L-Lys/L-Tyr/L-Arg TCT and no-pickling tanning process, the evident lower in five days' biochemical oxygen demand (BOD5 ), chemical oxygen demand (COD), total solids (TS), dissolved solids (DS) and suspended solids (SS) content were studied from EIA. The eco-friendly materials and cleaner tanning process can promote the sustainable development of the leather industry and reduce hazardous impacts on ecological environment. Highlights: The novel chemical synthesized with natural amino acid and cyanuric chloride is eco-friendly organic tanning agent. The tanning agent was applied to no-pickling tanning process of delimed and bated hides. The properties of tanned leather satisfied the basic demand of leather, and it is the good wet-white leather. The eco-friendly materials and cleaner tanning process reduce hazardous impacts on ecological environment.